1988
DOI: 10.1097/00000658-198802000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Ultrasonographic Localization of Islet Cell Tumors

Abstract: The purpose of the present study was to evaluate prospectively the value of intraoperative ultrasound scanning (IOUS) in localizing islet cell tumors by comparing results of IOUS to those of palpation during 44 consecutive laparotomies for gastrinoma (36) or insulinoma (8). All patients had preoperative radiographic imaging studies and selective venous sampling for hormones, which guided the subsequent laparotomy. Any suspicious finding by palpation and/or IOUS was resected. Pathologic evidence of islet cell n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0
12

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(114 citation statements)
references
References 15 publications
4
98
0
12
Order By: Relevance
“…211. 31 As for the other indications for IOUS, the findings of this study agree with those from literature, in terms of its use for the detection of pancreatic anatomic alterations, identification of the Wirsung duct, evaluation of texture, and the observation of peripancreatic vascular structures.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…211. 31 As for the other indications for IOUS, the findings of this study agree with those from literature, in terms of its use for the detection of pancreatic anatomic alterations, identification of the Wirsung duct, evaluation of texture, and the observation of peripancreatic vascular structures.…”
Section: Discussionsupporting
confidence: 90%
“…Ill. 311. 31 In the present study, IOUS provided additional data', as compared to other preoperative examinations (35.5 percent of the cases of neuroendocrine tumors). According to literature, the sensitivity of preoperative US/CT in detecting neuroendocrine tumors is fairly variable, ranging from 30 to 80 percent.…”
Section: Discussionmentioning
confidence: 66%
“…Because these modalities are not accurate enough for preoperative visualization and identification of PNETs in the pancreas, which is paramount in planning the extent of surgery, intraoperative ultrasound (IOUS) has been used for direct examination of the pancreas (20). In this study (20), IOUS was found to localize 96% of PNETs and 58% of non-PNETs. The authors concluded that IOUS altered surgical management in 11% of gastrinomas, mainly by identifying additional gastrinomas or determining that the gastrinoma was malignant.…”
Section: Discussionmentioning
confidence: 84%
“…However, there are pitfalls in localizing small tumours and tumours that lack somatostatin receptors (19). Because these modalities are not accurate enough for preoperative visualization and identification of PNETs in the pancreas, which is paramount in planning the extent of surgery, intraoperative ultrasound (IOUS) has been used for direct examination of the pancreas (20). In this study (20), IOUS was found to localize 96% of PNETs and 58% of non-PNETs.…”
Section: Discussionmentioning
confidence: 86%
“…Perioperative ultrasound may sometimes help in confirming the tumor (Norton et al, 1988). If localization of the tumor would not make possible enucleation due to close proximity of the vessels, resection is decided.…”
Section: Surgical Treatmentmentioning
confidence: 99%